Relationship Between Stress Levels and Hypertension Incidents in Menopous Age Female Prisoners in Class II A Tanjung Gusta Women's Prison Medan - Lianto, Naja Rahma; Lukito, Alamsyah; Ismurrizal, Ismurrizal; Sitepu, Dovi Camela (PT Inovasi Pratama Internasional, 2025)
Background: Hypertension in women is one of the effects of menopause, because there is a decrease in the hormone estrogen and an increase in the hormone cortisol. Women who have entered menopause tend to be easily stressed and cause an increase in blood pressure. One of the groups that is vulnerable to stress is female inmates. Objective: To determine the relationship between stress level and the incidence of hypertension in female inmates of menopausal age in class II A women's prison Tanjung Gusta, Medan. Methods: This study is an analytical research, with a cross sectional research design. Sampling in this study uses a purposive sampling technique. The respondents in this study were 62 people. The instrument used was a Sphygmomanometer to measure blood pressure and for measuring stress levels with the Perceived Stress Scale-10 (PSS-10) questionnaire. Results: In this study, the results of the Somer’s D test (p=0,259) were obtained, which showed that there was no significant relationship between stress levels and the incidence of hypertension in female inmates of menopausal age in class II A women's prison in Tanjung, Gusta Medan. Conclusion: There was no significant relationship between stress levels and the incidence of hypertension in female inmates of menopausal age in class II A women's prison in Tanjung, Gusta Medan.